2014
DOI: 10.1371/journal.pone.0092587
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Positive Selection in Mitochondrial Complexes I and V of the African Elephant

Abstract: As species evolve, they become adapted to their local environments. Detecting the genetic signature of selection and connecting that to the phenotype of the organism, however, is challenging. Here we report using an integrative approach that combines DNA sequencing with structural biology analyses to assess the effect of selection on residues in the mitochondrial DNA of the two species of African elephants. We detected evidence of positive selection acting on residues in complexes I and V, and we used homology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 67 publications
2
36
0
1
Order By: Relevance
“…In this study, we detected 47 amino acid sites that were in-651 fluenced by positive selection during intraspecific divergence of 652 M. zibellina. Among them, 23 were clade-specific mutations detected 653 mainly in the ND2, ND4, ND5 and CYTB proteins.654 Our results are in line with other studies that have found evidence of 655 adaptive evolution in the electron transport chain complexes (da 656Fonseca et al, 2008;Finch et al, 2014;Garvin et al, 2011). Garvin657 et al (2011) detected a strong signal of positive selection in the ND2 658 and ND5 genes between species of Pacific salmon.…”
supporting
confidence: 80%
“…In this study, we detected 47 amino acid sites that were in-651 fluenced by positive selection during intraspecific divergence of 652 M. zibellina. Among them, 23 were clade-specific mutations detected 653 mainly in the ND2, ND4, ND5 and CYTB proteins.654 Our results are in line with other studies that have found evidence of 655 adaptive evolution in the electron transport chain complexes (da 656Fonseca et al, 2008;Finch et al, 2014;Garvin et al, 2011). Garvin657 et al (2011) detected a strong signal of positive selection in the ND2 658 and ND5 genes between species of Pacific salmon.…”
supporting
confidence: 80%
“…This suggests natural selection on Lycaon metabolic processes e.g. [35, 36], which is likely given their unique antelope hunting strategies and diet. Moreover, these results are consistent with African wild dogs’ very high metabolic rate and hunting energy expenditure in comparison to domestic dogs [37].…”
Section: Resultsmentioning
confidence: 99%
“…With respect to ND1 subunit, mutations were found in residues located at protein-protein binding sites. Mutations in ND1 have been previously implicated in influencing metabolic efficiency in varied species including salmons (Consuegra, John, Verspoor, & Leaniz, 2015) and African elephants (Finch, Zhao, Korkin, Frederick, & Eggert, 2014). Moreover, mutations in binding sites may affect protein-protein interaction during complex assembly and translocation process (Brender & Zhang, 2015).…”
Section: Discussionmentioning
confidence: 99%